CORN - BRACHIARA CONSORTIUM (REMUNOM, 2024)
The maize-Brachiaria consortium has emerged as a highly efficient and sustainable agricultural practice in Brazil. This system integrates maize cultivation with Brachiaria pasture establishment, optimizing resource use and providing agronomic and economic benefits. The deep-rooted Brachiaria improves soil structure, water retention, and weed control while reducing herbicide needs. Additionally, Brachiaria’s allelopathic properties and ability to sequester carbon contribute to sustainability. This consortium enhances productivity, lowers input costs, and mitigates climate risks, making it an ideal model for sustainable agriculture.